Islamic Family Conflict Resolution In Malaysia, Family Conflict Resolution Mechanism Through Negotiation (Majlis Sulh) - Muhammad Zulkifli*, Zurfathin Aqilah Binti; Mukhsin, Abd (Riwayat: Educational Journal of History and Humanities, 2023)
This research discusses alternative Islamic family conflict resolution through sulh, the implementation process and its success in the Syariah Court. This research is a qualitative research with a normative juridical approach based on Malaysian legislation and Islamic law. Islam advocates peace in every conflict that occurs through the concept of ridha and tolerance. Sulh is one of the effective alternatives to conflict resolution through peace in the community other than through court proceedings which require longer time and higher costs. The successful implementation of sulh in the Syariah Court is evidence that this method is able to reduce cases pending in the Syariah Court over the years. The increase in cases that have been successfully resolved through the sulh method has increased the reputation of the Syariah Court among the community.